RF heating measurement using MR thermometry and field monitoring: Methodological considerations and first in vivo results. Issue 3 (16th September 2020) - Le Ster, Caroline; Mauconduit, Franck; Mirkes, Christian; Bottlaender, Michel; Boumezbeur, Fawzi; Djemai, Boucif; Vignaud, Alexandre; Boulant, Nicolas
Abstract : Purpose: A MR thermometry (MRT) method with field monitoring is proposed to improve the measurement of small temperature variations induced in brain MRI exams. Methods: MR thermometry experiments were performed at 7 Tesla with concurrent field monitoring and RF heating. Images were reconstructed with nominal k‐space trajectories and with first‐order spherical harmonics correction. Experiments were performed in vitro with deliberate field disturbances and on an anesthetized macaque in 2 different specific absorption rate regimes, that is, at 50% and 100% of the maximal specific absorption rate level allowed in the International Electrotechnical Commission normal mode of operation. Repeatability was assessed by running a second separate session on the same animal. Results: Inclusion of magnetic field fluctuations in the reconstruction improved temperature measurement accuracy in vitro down to 0.02°C. Measurement precision in vivo was on the order of 0.15°C in areas little affected by motion. In the same region, temperature increase reached 0.5 to 0.8°C after 20 min of heating at 100% specific absorption rates and followed a rough factor of 2 with the 50% specific absorption rate scans. A horizontal temperature plateau, as predicted by Pennes bioheat model with thermal constants from the literature and constant blood temperature assumption, was not observed. Conclusion: Inclusion of field fluctuations in image reconstruction was beneficial for the measurement of small temperature rises encountered in standard brain exams. More work is needed to correct for motion‐induced field disturbances to extract reliable temperature maps.